2007
DOI: 10.1016/j.jpaa.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Generic initial ideals and graded Artinian-level algebras not having the Weak-Lefschetz Property

Abstract: We find a sufficient condition that H is not level based on a reduction number. In particular, we prove that a graded Artinian algebra of codimension 3 with Hilbert function, and also prove that any codimension 3 Artinian graded algebra A = R/I cannot be level if β 1,d+2 (Gin(I )) = β 2,d+2 (Gin(I )). In this case, the Hilbert function of A does not have to satisfy the conditionMoreover, we show that every codimension n graded Artinian level algebra having the Weak-Lefschetz Property has a strictly unimodal Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 35 publications
1
28
0
1
Order By: Relevance
“…This is true even for level algebras, since, for instance, it can be shown that h = (1, 13, 13, 14) is a level h-vector, but h clearly fails to be differentiable from degree 2 to degree 3. (To construct this level h-vector, one can start with Stanley's well-known non-unimodal Gorenstein h-vector (1,13,12,13,1) and add the fourth power of a general linear form in the same variables to the inverse system to get (1,13,13,14,2), and then truncate.) Theorem 3.4 also carries a consequence concerning the WLP, since it provides an indirect way to construct algebras without the WLP.…”
Section: Differentiability and Unimodalitymentioning
confidence: 99%
See 4 more Smart Citations
“…This is true even for level algebras, since, for instance, it can be shown that h = (1, 13, 13, 14) is a level h-vector, but h clearly fails to be differentiable from degree 2 to degree 3. (To construct this level h-vector, one can start with Stanley's well-known non-unimodal Gorenstein h-vector (1,13,12,13,1) and add the fourth power of a general linear form in the same variables to the inverse system to get (1,13,13,14,2), and then truncate.) Theorem 3.4 also carries a consequence concerning the WLP, since it provides an indirect way to construct algebras without the WLP.…”
Section: Differentiability and Unimodalitymentioning
confidence: 99%
“…(We have already seen an example in socle degree 4 above, but we give a different one now.) (1,8,16,24,36). Since the first difference is (1,7,8,8,12), which is not an O-sequence (since 12 > (8 (3) ) 1 1 = 10), we obtain our desired example.…”
Section: Differentiability and Unimodalitymentioning
confidence: 99%
See 3 more Smart Citations